Регіональна етнополітика в Україні: ризики та виклики соціальній стабільності - Бурдяк, Віра (My University, 2009)
In the article development of ethnic political relations in Ukraine during the years of independence are analyzed; risks and traps which exist in this sphere in our state as well as in any other state with multiethnic population are pointed out; peculiar miscal-culations in the legislation regarding the development of ethnic communities are discerned. It is emphasized that minimization of ethnic political threats to the social stability should be among the priorities of ethnic policy.
Keywords: етнополітика; регіональна етнополітика; Україна